Progresso genético para produção de grãos obtido em doze anos de melhoramento da população elite de arroz de terras altas - Barros, Matheus Souza de (2015)
The genetic improvement resulted from plant breeding acts decisively in maintaining the supply of agricultural foods like rice. The contribution of this genetic improvement to increase productivity is expressed in many crops by genetic progress which represents the genetic changes in the course of the selection cycles, and promotes the advance of genotypic average towards selection. Among the strategies adopted to increase the gain by selection, the early generation selection proves to be promising. This work has aimed to evaluate the genetic potential for selecting upland rice progenies and estimate the genetic progress for grain yield. The data used in this study were obtained from the progeny yield trials conducted in the period of eleven agricultural years 2002/03 to 2012/13 conducted by Embrapa Rice and Beans. The traits analyzed were grain yield (kg ha-1), plant height (cm) and days to flowering (day). In each year of the experiment, a group of progeny was tested in four to six sites. It was used Federer's augmented block design without replication per site in seven years and with at least three checks, in four years of the series were used two replications. The experimental data within each year were submitted to joint analysis. A mixedeffects linear model was applied for estimating the components of variance by the method of restricted maximum likelihood (REML). From this estimate of the components, it was calculated the genetic and phenotypic parameters, in addition the selective accuracy, the experimental precision coefficient, the experimental variation coefficient and relative variation coefficient. The genetic progress was estimated by the method of generalized linear regression of the adjusted means of progeny groups evaluated in each year by the mixed model approach. The estimates of the relative annual mean gain and the total relative gain for the three studied traits were also obtained. The estimates of genetic variance among progenies for grain yield were highly significant (p < 0.001), except for the progeny group evaluated in 2007. The heritability estimation ranging from 0.22 to 0.69 that, associated with the selective accuracy, indicates the expected level of efficiency with early generation selection in each group of progenies. For Plant height and daysto- flowering, the genetic variance estimates were significant (p ≤ 0.01) in all groups. The variance components for these traits led to a rather high heritability estimation that suggests favorable conditions for selection in early generations. The genetic progress for grain yield (80.5 kg ha-1 yr-1) was highly significant. This value represents a relative annual mean gain of 2.88%. Throughout the period, the cumulative gain was estimated in 32.86% which indicates an increase of 918 kg ha-1 for grain yield. The response for plant height was not significant, suggesting that the height of progenies remained stable over the period. For days-to-flowering, it was detected significant increase in cycle length, indicated by the cumulative increase of the vegetative period in about five days (6.73%). From these results we conclude that early generation selection, adopted by the breeding program, were effective in promoting the genetic gain for grain yield in the elite populations.